Practice-based Learning Across and Between the Health professions: A Conceptual Exploration of Definitions and Diversity and their Impact on Interprofessional Education - Thistlethwaite, Jill E. (International Journal of Practice-based Learning in Health and Social Care, 2016)
Practice-based learning (PrBL) occurs in all health professional training but there are intra- and interprofessional differences depending on context, location and professional identity. In this position paper I will explore the definition, context and elements of PrBL across the health professions, and their implications for interprofessional education (IPE). IPE is a particular focus because of its increasing prominence globally in response to the changing nature of health care delivery as the population ages, the incidence of long term and chronic conditions increases and health and social care delivery is undertaken increasingly in multidisciplinary teams. PrBL aims to facilitate the transfer of theory into the workplace through situated and experiential learning. But it is not solely about preparing for practice after qualification; rather it is about learning in and about practice through authentic experience and becoming part of a community of practice. Best PrBL requires the alignment of explicit learning outcomes with clinically situated and supervised learning activities, and then with valid and reliable assessment. There are still questions about the optimal length and timing of rotations/attachments, and the nature of work-based assessment. The majority of an individual student’s PrBL is uniprofessional but there is a global trend towards increasing and enhancing the provision of interprofessional PrBL, despite the logistical and resource implications. This paper is an overview of current trends in PrBL and raises questions about future research and developments. ‘In everyday organizational life, work, learning, innovation, communication, negotiation, conflict over goals, their interpretation, and history, are co-present in practice. They are part of human existence’ (Gherardi 2000, p214). In this position paper I explore the aims, nature and delivery of practice-based learning (PrBL) in order to introduce the scope of the journal and consider areas for further exploration.